The Application of Geographical Information System for Social Sciences in Interdisciplinary Studies - Farah, Zaini; Adibah, Yusuf; Siti Khatijah, Zamhari (2020)
Geographical Information System (GIS) and social sciences are two different fields but can be integrated through interdisciplinary research. With the advancement of technology, GIS technological tools can assist the social sciences research by enabling spatial relation. By looking at the importance of GIS, UNIMAS has taken a step ahead by introducing the GIS technology to social sciences student, in Development Planning and Management Program. The main purpose is to equip students with technological tools which can be their added value. However, during the implementation, the difficulties in bridging the gap between both fields occur since this technology is not familiar with. The aim of this article is to examine how GIS education and Social Sciences integrate focusing on output from the field-work experience. Thus, this article discussed the importance of GIS in social science and the students’ performance in this integration. The respondents were brought to a field trip which integrates both GIS and social science study. This study is a qualitative study. The respondents’ perceptions were analysed using thematic analysis and hands-on practical outputs in the GIS lab were reviewed. As a result, respondents view on the application of GIS in the social sciences field is limited to the basic function, not in the application widely. Meanwhile, the hands-on practical output shows that the respondents managed to integrate the data from the fieldwork to digital data, however, it is slightly inaccurate. In summary, the aim of this study on integration GIS and social sciences field is achieved where it is a good opportunity to integrate both fields to be an eye-opener. However, proper planning needs to be set up to maximizing the function of GIS in social sciences research field.